Tamm Review: Reforestation for resilience in dry western U.S. forests - North, Malcolm P.; Stevens, Jens T.; Greene, David F.; Coppoletta, Michelle; Knapp, Eric E.; Latimer, Andrew M.; Restaino, Christina M.; Tompkins, Ryan E.; Welch, Kevin R.; York, Rob A.; Young, Derek J.N.; Axelson, Jodi N.; et al. (Forest ecology and management, 2019)
•Current reforestation often focuses on planting regularly-spaced pine seedlings.•‘Course correction’ depends on increasingly rare follow-up treatments.•This approach may not build early resilience to fire and drought stress.•An alternative is suggested that includes dividing replanting areas into three zones.•We also emphasize including cluster planting in mesic microsites.•Using prescribed fire to reduce fuels, competing vegetation and build resilience.•Limitations and areas that need further research are highlighted. The increasing frequency and severity of fire and drought events have negatively impacted the capacity and success of reforestation efforts in many dry, western U.S. forests. Challenges to reforestation include the cost and safety concerns of replanting large areas of standing dead trees, and high seedling and sapling mortality rates due to water stress, competing vegetation, and repeat fires that burn young plantations. Standard reforestation practices have emphasized establishing dense conifer cover with gridded planting, sometimes called 'pines in lines', followed by shrub control and pre-commercial thinning. Resources for such intensive management are increasingly limited, reducing the capacity for young plantations to develop early resilience to fire and drought. This paper summarizes recent research on the conditions under which current standard reforestation practices in the western U.S. may need adjustment, and suggests how these practices might be modified to improve their success. In particular we examine where and when plantations with regular tree spacing elevate the risk of future mortality, and how planting density, spatial arrangement, and species composition might be modified to increase seedling and sapling survival through recurring drought and fire events. Within large areas of contiguous mortality, we suggest a “three zone” approach to reforestation following a major disturbance that includes; (a) working with natural recruitment within a peripheral zone near live tree seed sources; (b) in a second zone, beyond effective seed dispersal range but in accessible areas, planting a combination of clustered and regularly spaced seedlings that varies with microsite water availability and potential fire behavior; and (c) a final zone defined by remote, steep terrain that in practice limits reforestation efforts to the establishment of founder stands. We also emphasize the early use of prescribed fire to build resilience in developing stands subject to increasingly common wildfires and drought events. Finally, we highlight limits to our current understanding of how young stands may respond and develop under these proposed planting and silvicultural practices, and identify areas where new research could help refine them.